Therapeutic effects of NAC and CoQ10 on aluminium phosphide poisoning as an adjuvant therapy: A Pilot study - Maii Farag Henaidy; Maha Ghanem; Shehata Farag Shehata; Amal M. Shouair; Reda R. Mabrouk (Toxicology Reports)
In aluminium phosphide (AlP) poisoning, death is mainly due to acute heart failure. There is some evidence showing that N-acetylcysteine (NAC) and coenzyme Q10 have antioxidant and cardioprotective effects. This study investigated a new approach for treating acute AlP poisoning by using NAC and Co-Q10 as adjuvant therapy. Subjects and methods: The study design was a retrospective-prospective study. It was conducted in the poisoning unit of Kafer Eldwar General Hospital. Sixty patients with acute aluminium phosphide poisoning were included. The patients were divided into two groups. The first group (standard protocol) considered the control group received the standard supportive care, and their data were collected from the medical records. The second group (new protocol) in addition to the standard supportive care received the NAC and CoQ10 regimen, and all data were collected in a specially designed sheet. Results: The results showed that the highest percentage of patients in both groups were aged 18–25, followed by those under 18, and females outnumbered the males. The systolic (SBP) and diastolic (DBP) blood pressure showed significant improvement in the new protocol group. A significant statistical difference was found between the two groups regarding mechanical ventilation (p = 0.015), where mechanical ventilation was used in 20 % of patients in the new protocol group and 50 % in the standard group. Regarding the outcome of patients, the survival rate reached 73.3 % upon using the new protocol, compared to 50 % who received the standard protocol. Conclusion: The data imply that further investigation in using the NAC and CoQ10 regimen is warranted. It gave an improvement of the survival rate and decrease the need for mechanical ventilation in AlP